2011
DOI: 10.1177/2040622311415895
|View full text |Cite
|
Sign up to set email alerts
|

Age-related macular degeneration: current treatment and future options

Abstract: Age-related macular degeneration is the leading cause of visual impairment among older adults in the developed world. Epidemiological studies have revealed a number of genetic, ocular and environmental risk factors for this condition, which can be addressed by disease reduction strategies. We discuss the various treatment options for dry and exudative age-related macular degeneration available and explain how the recommended treatment depends on the exact type, location and extent of the degeneration. Currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…Age-related macular degeneration (AMD) is a neurodegenerative disease that leads to deficiencies of retinal pigment epithelium (RPE) and, consequently, reduction in visual function [1]. The RPE is a single layer of cells adjacent to the outer segment of photoreceptor of the retina and Bruch's membrane [2].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) is a neurodegenerative disease that leads to deficiencies of retinal pigment epithelium (RPE) and, consequently, reduction in visual function [1]. The RPE is a single layer of cells adjacent to the outer segment of photoreceptor of the retina and Bruch's membrane [2].…”
Section: Introductionmentioning
confidence: 99%
“…Age-related macular degeneration (AMD) is a vision-threatening ocular disease affecting the macular region of the retina, retinal pigment epithelium (RPE), Bruch's membrane, and choriocapillaries (1). The disease is typically manifested in two forms: "dry" and "wet."…”
Section: Introductionmentioning
confidence: 99%
“…Despite proven to be efficacious [29, 30], concerns have been raised regarding the safety of this drug due to the implications of VEGF in thrombus formation and development of atherosclerotic plaques [28]. To address these concerns, studies were conducted to identify the risk of exposure to cardiovascular events such as thrombosis, hypertension, and haemorrhage.…”
Section: Present Treatments For Neovascular Amdmentioning
confidence: 99%
“…In addition, it is less affinity matured than ranibizumab but binds to more isoforms of VEGF [28]. Through large clinical trials, bevacizumab has demonstrated similar efficacy and safety results as ranibizumab [32, 33].…”
Section: Present Treatments For Neovascular Amdmentioning
confidence: 99%